ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA UMKM DI BIDANG PANGAN PADA KABUPATEN LOMBOK UTARA PADA MASA PANDEMI COVID-19 - Anna Apriana Hidayanti; Eka Nurminda Dewi Mandalika (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2022)
The main objective of this study was to analyze the effect of technological sophistication, management participation, user technical skills, and the application of accounting information systems to the performance of MSMEs in the food sector in North Lombok Regency during the co-19 pandemic. The type of data used is quantitative data which includes data on the score of the collected questionnaire answers. The method used in this research is purposive sampling method. The sample that met the criteria in this study was 31 MSMEs. The data processing methods used are descriptive analysis, validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination test, F test, and t test. The results showed that technological sophistication, user technical ability and application of accounting information systems had a positive and significant effect on MSME performance. To test the coefficient of determination, the adjusted R2 value is that the performance of MSMEs is influenced by technological sophistication, technical capabilities of users and the application of accounting information systems by 38%, while the remaining 68.4% is influenced by other factors not examined in this study.